Measuring dysfunctional grief due to a COVID-19 loss: A Turkish validation study of the Pandemic Grief Scale. Issue 1 (2nd January 2022) - Evren, Cuneyt; Evren, Bilge; Dalbudak, Ercan; Topcu, Merve; Kutlu, Nilay
Abstract: The global death toll to date of the COVID-19 pandemic has been enormous, and millions of people are grieving these losses. The aim of the current study is to validate a Turkish version of the Pandemic Grief Scale (PGS), which is a brief English-language mental health screener to identify probable cases of dysfunctional grief associated with a COVID-19 death. Participants were assessed using the PGS, Patient Health Questionnaire-4 (PHQ-4) and Work and Social Adjustment Scale (WSAS). We surveyed 758 Turkish native speakers who participated online. Confirmatory factor analysis showed that the factor structure of the PGS was satisfactory. The scale was internally consistent with a Cronbach's alpha of 0.77 and a composite reliability of 0.90. The PGS demonstrated construct validity with strong correlations with suicidal ideation and substance use coping. Positive correlations of the PGS with the PHQ-4 and the WSAS demonstrated adequate convergent validity. The PGS discriminates well between persons with and without dysfunctional grief using an optimized cut score of ≥ 3 (89% sensitivity and 72% specificity). The PGS also demonstrates incremental validity by explaining most of the variance (43%) in functional impairment due to a COVID-19 loss beyond measures of depression and generalized anxiety. These findings closely replicate the original validation study on the PGS in English and suggest that the current Turkish version of the PGS is a valid and reliable measure to assess the severity of dysfunctional grief associated with a COVID-19 death.